Lagovirus europeus GI.2 (rabbit hemorrhagic disease virus 2) infection in captive mountain hares (Lepus timidus) in Germany - Buehler, Melanie; Jesse, Sonja T.; Kueck, Heike; Lange, Bastian; Koenig, Patricia; Jo, Wendy K.; Osterhaus, Albert; Beineke, Andreas (figshare, 2020)
Abstract Background Rabbit hemorrhagic disease virus (RHDV, Lagovirus europeus GI.1) induces a contagious and highly lethal hemorrhagic disease in rabbits. In 2010 a new genotype of lagovirus (GI.2), emerged in Europe, infecting wild and domestic population of rabbits and hares. Case presentation We describe the infection with a GI.2 strain, “Bremerhaven-17”, in captive mountain hares (Lepus timidus) in a zoo facility in Germany. Postmortem examination revealed RHD-like lesions including necrotizing hepatitis. RT-qPCR and AG-ELISA confirmed presence of GI.2. Recombination and phylogenetic analysis grouped the identified strain with other GI.2 strains, sharing nucleotide identity of 91–99%. Conclusion Our findings confirm that mountain hares are susceptible to GI.2 infection, due to a past recombination event facilitating virus spillover from sympatric rabbits.